The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1373/clinchem.2008.108647
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 8 HIV-Protease Inhibitors and 2 Nonnucleoside Reverse Transcriptase Inhibitors by Ultra-Performance Liquid Chromatography with Diode Array Detection

Abstract: BACKGROUND:Most HPLC-UV methods for therapeutic drug monitoring of anti-HIV drugs have long run times, which reduce their applicability for highthroughput analysis. We developed an ultra-performance liquid chromatography (UPLC)-diode array detection method for the simultaneous quantification of the HIV-protease inhibitors (PIs) amprenavir, atazanavir, indinavir, lopinavir, nelfinavir, ritonavir, saquinavir, and tipranavir (TPV), and the nonnucleoside reverse transcriptase inhibitors (NNRTIs) efavirenz and nevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…The retention time of the internal standard was 2.996 min. The total run time was 9.5 min, shorter than the 14 min described by Elens et al 20 in the only previously published UPLC assay for anti-HIV drugs. The longer chromatographic analysis of Elens et al 20 included the measurement of the late eluting protease inhibitor tipranavir, which was not present in our assay because this drug is not registered in Brazil, being excluded of the recommended therapeutic schemes of the Brazilian Ministry of Health.…”
Section: Chromatography and Sample Preparationmentioning
confidence: 73%
See 2 more Smart Citations
“…The retention time of the internal standard was 2.996 min. The total run time was 9.5 min, shorter than the 14 min described by Elens et al 20 in the only previously published UPLC assay for anti-HIV drugs. The longer chromatographic analysis of Elens et al 20 included the measurement of the late eluting protease inhibitor tipranavir, which was not present in our assay because this drug is not registered in Brazil, being excluded of the recommended therapeutic schemes of the Brazilian Ministry of Health.…”
Section: Chromatography and Sample Preparationmentioning
confidence: 73%
“…The longer chromatographic analysis of Elens et al 20 included the measurement of the late eluting protease inhibitor tipranavir, which was not present in our assay because this drug is not registered in Brazil, being excluded of the recommended therapeutic schemes of the Brazilian Ministry of Health. 23,24 However, the retention times of Elens et al 20 were higher for all drug common for both assays: 4.844 for nevirapine, 8.033 for indinavir, 9.479 for amprenavir, 9.506 for saquinavir, 10.287 for atazanavir, 10.502 for efavirenz, 10.880 for lopinavir and 10.887 for ritonavir, with only partial resolution of these two analytes. Moreover, these authors employed an internal standard not commercially available, what reduces the practical application of the method.…”
Section: Chromatography and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several LC-MS/MS methods described in the literature were developed for simultaneous quantification of various anti-HIV agents with a long analytical time. 16,24,26,27,29,43 This method for quantitation of efavirenz in human plasma show an analytical time of 2.0 min and was successfully applied in a bioequivalence study. The use of mass spectrometric detection in MRM mode is less demanding on chromatographic separation between analytes and early-eluting interferents due to improved selectivity and this feature can be explored to increase sample throughput by reducing sample analysis time, provided adequate selectivity without ion suppression is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods described in the literature for the quantitative analysis of atazanavir in plasma, either alone [5][6][7] or in combination with other ARVs [7][8][9][10]. Some authors reported the use of mass spectrometry for detection [10], which is not routinely available in all laboratories.…”
Section: Introductionmentioning
confidence: 99%